Compassion Fatigue in Pediatric Emergency Department Staff. Issue 11 (November 2019) - Nilan, Laura M.; Patel, Lina; Moffatt, Mary E.; Linebarger, Jennifer S.; Sherman, Ashley K.; Randell, Kimberly A.
Abstract : Introduction: Compassion fatigue, a product of burnout (BO), secondary traumatic stress (STS), and compassion satisfaction (CS), is reduced capacity and interest in being empathetic for suffering individuals. Our objective was to determine prevalence of compassion fatigue in the pediatric emergency department. Methods: We administered the Professional Quality of Life instrument, including BO, STS, and CS scales, to a convenience sample of pediatric emergency department staff (physicians, nurses, technicians, social workers, child life specialists). We categorized participants as having BO (high BO, low CS, moderate-low STS scores), STS (high STS, moderate-low BO, low CS), compassion fatigue (high STS and BO, low CS), and high-risk fatigue (high STS, moderate-low BO, low CS) and low risk (moderate-high CS, moderate-low BO, low STS) of compassion fatigue. Results: One hundred seventy-seven staff (50% response rate) participated. The majority were white (90%) and female (88%), with participation highest among physicians (97%). Twenty-six percent had low CS scores, 26% had high BO scores, and 20% had high STS scores. Five percent met criteria for categorization as compassion fatigue, 24% for BO, and 24% for low risk of compassion fatigue. Current personal stress was associated with higher BO scores ( P = 0.008) and secondary categorization as BO ( P = 0.05). Recent work stress was associated with high STS scores ( P = 0.03). Discussion: Five percent of participants met criteria for compassion fatigue; a significant proportion had BO, STS, or CS scores, placing them at risk of compassion fatigue. Future studies should explore factors contributing to and interventions to minimize compassion fatigue.